2012
DOI: 10.1111/j.1476-4431.2012.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of presenting temperature of urethral obstructed male cats and the association with severity of azotemia and length of hospitalization: 243 cats (2006–2009)

Abstract: No association with regard to rectal temperature and LOH could be demonstrated in this population of cats. However, the presence of azotemia in obstructed male cats appears to provide the clinician with additional information regarding the necessary LOH and eventual cost to the client.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…A retrospective study evaluating rectal temperatures of male cats with urethral obstruction found that BUN and serum creatinine concentrations were significantly higher in the hypothermic group. 16 Another study investigating prognostic factors for cats with AKI found lower body temperature to be a useful predictor of death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study evaluating rectal temperatures of male cats with urethral obstruction found that BUN and serum creatinine concentrations were significantly higher in the hypothermic group. 16 Another study investigating prognostic factors for cats with AKI found lower body temperature to be a useful predictor of death.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 There is also a trend toward longer hospital stays in hypothermic cats with urethral obstruction. 16 It has, thus, become increasingly important to continue investigating UH.…”
mentioning
confidence: 99%
“…Uremic hypothermia also is addressed in the veterinary literature, albeit less directly. A retrospective study evaluating rectal temperatures of male cats with urethral obstruction found that BUN and serum creatinine concentrations were significantly higher in the hypothermic group . Another study investigating prognostic factors for cats with AKI found lower body temperature to be a useful predictor of death .…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study evaluating rectal temperatures of male cats with urethral obstruction found that BUN and serum creatinine concentrations were significantly higher in the hypothermic group. 16 Another study investigating prognostic factors for cats with AKI found lower body temperature to be a useful predictor of death. 14 In another study of cats with AKI treated by hemodialysis, the prevalence of hypothermia was high at 64%, making hypothermia one of the most common abnormalities detected on physical examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation